Shifting Gears: Redefining the Roadmap for America's Auto Industry - Giglio, Joseph M.; Chieppo, Charles D. (Archives of Business Research, 2025)
The American automobile industry has always been more than just a provider of transportation – it’s an engine of economic growth, job creation and technological innovation. Today the industry sits at the intersection of unprecedented technological transformation and turbulent geopolitical pressures. As we approach 2030, electrification, automation and connectivity are reshaping the landscape. At the same time, firms like Uber and Lyft are changing the nature of vehicle ownership. Members of Gen Z in particular don’t attach the same importance to vehicle ownership that their forbears did. But as technology pushes ahead, policy choices on issues such as global trade, tariffs and domestic electric vehicle policies could either accelerate progress or create obstacles to it. This article advocates for policies that resist outdated models of protectionism and short-term politics in favor of ones that promote the industry’s ability to adapt to changes that will outlive the politics of the moment and continue to deliver innovation in a future that will be marked by electrification and autonomous vehicles.